The effects of default nudges on promoting approval of welfare cuts: An exploration during COVID-19 - Liu, Xin; Zhao, Ning; Zheng, Rui (Frontiers in Psychology, 2023)
The global COVID-19 pandemic has created significant financial and operational challenges for some businesses. As a result, temporary welfare benefit reduction may be a tough but future-oriented choice for both employers and employees. The present study examined whether default nudges can be used to promote employees’ approval of welfare-cutting policy while avoiding negative attitudes. Two online surveys were conducted during the first pandemic wave in China (February 2020). In the first study (N = 310), the participants were presented with a hypothetical welfare-cutting policy that used either an opt-in approach or an opt-out approach. We aimed to investigate how their approval and attitudes were different between two conditions. The results showed that the employees in the opt-out condition were more likely to accept the welfare-cutting policy than those in the opt-in condition, while participants’ attitudes toward the policy employing opt-out approach were as negative as that employing opt-in approach. Study 2 (N = 1,519) involved a replication of Study 1 with two additional improved opt-out approaches (opt-out education and opt-out transparency). Compared with the opt-in approach and standard opt-out approach, the opt-out education approach both increased policy support and improved attitudes toward the welfare-cutting policy. The theoretical and practical implications of these findings are discussed.